LITERASI KEUANGAN SEBAGAI MODERASI HUBUNGAN ANTARA PERILAKU DAN INKLUSI KEUANGAN TERHADAP KEPUTUSAN INVESTASI GENERASI Z - Rizqiandini, Anisa; Meiriyanti, Rita; Nastiti, Prianka Ratri (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2025)
This study aims to analyze the influence of financial behavior and financial inclusion on investment decisions, as well as the moderating role of financial literacy on the relationship among Generation Z in Batang Regency. The method used is quantitative with a Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS) through the SmartPLS 3 application. The results of this study indicate that financial behavior and financial inclusion have a positive and significant effect on investment decisions. In addition, financial literacy is proven to positively and significantly moderate the relationship between financial behavior and investment decisions, but does not moderate the relationship between financial inclusion and investment decisions. These findings indicate the importance of financial literacy in strengthening the impact of financial behavior on investment decisions, but not enough to strengthen the relationship between financial inclusion and investment decisions. This study provides implications for the development of a more comprehensive financial education strategy to encourage investment among the younger generation.